Increasing access to rural finance in Bangladesh : the forgotten "missing middle" - Ferrari, Aurora (Directions in development. Finance, 2008)
Since the mid-1990s, Bangladesh's banking sector has grown considerably. Despite the boom and the government's efforts to increase access in rural areas, rural financial markets have shrunk in relative terms. As a result, access to finance by micro, small, and medium-size enterprises and marginal, small, and medium-size farmers - the "missing middle" - remains limited, which is significant because these groups are the engines of growth in rural Bangladesh in terms of employment, contribution to GDP, and prospects for future growth. Increasing Access to Rural Finance in Bangladesh examines the legal, regulatory, and institutional constraints faced by state-owned agricultural banks, private banks, and microfinance institutions in providing financial services to the missing middle in Bangladesh. It also analyzes the constraints that traditional, multiperil crop inssurance schemes face when serving marginal, small, and medium-size farmers. Finally, the book offers suggestions to improve rural financial access with innovations and reforms in the banking, microfinance, and insurance sectors, among others